Cutting through the complexity: caesarean section with simultaneous salpingo-oophorectomy for mature dermoid cyst at term: a case report - Amreen, Syeda A.; Arakeri, Santosh; Gupta, Namita; Patil, Neelamma; Shiragur, Shobha; Mulimani, Srushti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Adnexal masses are identified in approximately 2 to 20 out of every 1,000 pregnancies a rate that is about 2 to 20 times higher than in non-pregnant individuals of the same age group. The most frequently encountered types during pregnancy include dermoid cysts (32%), endometriomas (15%), functional cysts (12%), serous cystadenomas (11%), and mucinous cystadenomas (8%). Malignancy occurs in about 2% of cases. Most adnexal masses in pregnancy can be safely observed, with nearly 70% resolving spontaneously. However, surgical intervention is occasionally required due to symptoms, suspected malignancy, or the risk of ovarian torsion. Ultrasound is the preferred imaging modality, valued for its safety, diagnostic accuracy, and widespread availability. Dermoid cysts, in particular, can present diagnostic and management challenges during pregnancy. When surgery is necessary, the second trimester is generally the optimal window, as it allows time for possible spontaneous resolution and offers better visualization conditions due to uterine size and anatomical positioning. Nevertheless, surgery should not be delayed solely based on gestational age when there is a clear clinical indication. When performed in a setting with appropriate obstetric, anaesthetic, and neonatal support, surgical management of adnexal masses during pregnancy is typically associated with favourable outcomes for both the patient and the fetus.